Negotiation of needs towards halal talents sustainability - Norhayati Rafida Abdul Rahim; Muhammad Nizam Awang; Abdullah, Ismail; Yahya, Noor Azrina; Muhammad, Siti Zubaidah; Ahmad Sabri, Safiyyah; Ahmad, Norfaizah Nadhrah (Emerald Group Holdings Ltd., 2024)
Indexed by WOS/SCOPUS/ERA